The Role of Perceived In-group Moral Superiority in Reparative Intentions and Approach Motivation - Szabó, Zsolt P.; Mészáros, Noémi Z.; Csertő, István (Frontiers in Psychology, 2017)
Three studies examined how members of a national group react to in-group wrongdoings. We expected that perceived in-group moral superiority would lead to unwillingness to repair the aggression. We also expected that internal-focused emotions such as group-based guilt and group-based shame would predict specific, misdeed-related reparative intentions but not general approach motivation toward the victim groups. In Study 1, facing the in-group’s recent aggression, participants who believed that the Hungarians have been more moral throughout their history than members of other nations, used more exonerating cognitions, experienced less in-group critical emotions and showed less willingness to provide reparations for the members of the victim group. Study 2 and Study 3 confirmed most findings of Study 1. Perceived in-group moral superiority directly or indirectly reduced willingness to provide either general or specific reparations, while internally focused in-group critical emotions predicted specific misdeed-related reparative intentions but not general approach motivation. The role of emotional attachment to the in-group is considered.